Performance Improvement of Hopper Cooling System on Traditional Fishing Boats Due to Excessive Cooling - Koenhardono, Eddy Setyo (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2020)
The engine cooling system that drives traditional fishing boats uses a hopper cooler type system that experiences excessive cooling. Ideally, the temperature of the cooling water in the hopper should be approximately 70-80°C. The fact, it is only 42°C, thus reducing the effective power generated by the engine. This excessive cooling may cause an increase in fuel consumption and emissions. One method to reduce excessive cooling is to increase the temperature of the cooling media in the hopper.  The author has conducted a simple experiment on a traditional fishing boat in Kenjeran, Surabaya, by installing a valve to control the flow of seawater entering the hopper. However, the use of seawater as a cooling medium has a maximum operating temperature limitation, so there is no precipitation of salt and lime, which is 50oC. At this temperature, the benefits are not large, only an increase in speed of 4.4% and a fuel reduction of 4.3%. Therefore, the existing seawater cooling system must be modified to an indirect seawater cooling system to get optimum performance improvement. The re-modification allows the temperature of the freshwater in the hopper to be maintained at 80°C, so that the speed of the fishing boat may increase by 14%, with a fuel savings of 12.3%.